Information and Resistence in the era of the transparency society: the reconstruction of democratic ethos e as a space of freedom. - de Souza, Gabriel Scudeller; Sabbag, Deise Maria Antonio [UNESP]; Achilles, Daniele (Universidade Federal de Santa Catarina (UFSC), 2022)
Objective: proposes to think about the importance of resistance, based on human negativity and fallibility, present in the dialectic that builds the individual and allows his emancipation, to provide the reconstruction of politics through subjective and institutional practices. Methods: This article, carried out under the deductive method, based on consultations with bibliographic instruments, reviews and other scientific materials, Results: Society walks guided by information and communication, especially from new technologies and the dissemination and use of social networks, and the appropriation of these technologies and informational raw material by large companies, which dominate the world scene from analysis and data extraction, used for market segmentation and rendering. Homogenizing forces of social domination work cohesive to the interests of capital, which is neoliberalism in the contemporary world, state structures work to satisfy their interests. Conclusions: From this perspective, there is interference with human rights and the democratic system, as well as the consecration of a new power device, which translates into a neoliberal psychopolitics. The issue of freedom is discussed from the manipulation and social control exercised by the holders of psychopower, which, in the end, seeks to break with banal spaces and, ultimately, with the idea of resistance, everything from bet on technique raised to maximum power. Institutionalized informational spaces can offer elements for the experience and practice of resistance and freedom for the construction and formation of the democratic ethos, as information has the dynamo of crossing and drift that makes it possible to find new paths, new places, invention, knowledge, and recognition.
INFORMAÇÃO E RESISTÊNCIA NA ERA DA SOCIEDADE DA TRANSPARÊNCIA: A RECONSTRUÇÃO DO ETHOS DEMOCRÁTICO ENQUANTO ESPAÇO DE LIBERDADE
Keywords: Democratic Ethos; Information and Democracy; Information and Resistance; Psychopolitics; Transparency Society